BLTR1 in Monocytes Emerges as a Therapeutic Target For Vascular Inflammation With a Subsequent Intimal Hyperplasia in a Murine Wire-Injured Femoral Artery - Baek, Seung E.; Park, So Y.; Bae, Sun S.; Kim, Koanhoi; Lee, Won S.; Kim, Chi D. (Frontiers in Immunology, 2018)
Given the importance of high-mobility group box 1 (HMGB1) and 5-lipoxygenase (5-LO) signaling in vascular inflammation, we investigated the role of leukotriene signaling in monocytes on monocyte-to-macrophage differentiation (MMD) induced by HMGB1, and on vascular inflammation and subsequent intimal hyperplasia in a mouse model of wire-injured femoral artery. In cultured primary bone marrow-derived cells (BMDCs) stimulated with HMGB1, the number of cells with macrophage-like morphology was markedly increased in association with an increased expression of CD11b/Mac-1, which were attenuated in cells pre-treated with Zileuton, a 5-LO inhibitor as well as in 5-LO-deficient BMDCs. Of various leukotriene receptor inhibitors examined, which included leukotriene B4 receptors (BLTRs) and cysteinyl leukotriene receptors (cysLTRs), the BLTR1 inhibitor (U75302) exclusively suppressed MMD induction by HMGB1. The importance of BLTR1 in HMGB1-induced MMD was also observed in BMDCs isolated from BLTR1-deficient mice and BMDCs transfected with BLTR1 siRNA. Although leukotriene B4 (LTB4) had minimal direct effects on MMD in control and 5-LO-deficient BMDCs, MMD attenuation by HMGB1 in 5-LO-deficient BMDCs was significantly reversed by exogenous LTB4, but not in BLTR1-deficient BMDCs, suggesting that LTB4/BLTR1-mediated priming of monocytes is a prerequisite of HMGB1-induced MMD. In vivo, both macrophage infiltration and intimal hyperplasia in our wire-injured femoral artery were markedly attenuated in BLTR1-deficient mice as compared with wild-type controls, but these effects were reversed in BLTR1-deficient mice transplanted with monocytes from control mice. These results suggest that BLTR1 in monocytes is a pivotal player in MMD with subsequent macrophage infiltration into neointima, leading to vascular remodeling after vascular injury.